If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -5(1 + -1p) = -5p + 3(1 + -1p) 2p + (1 * -5 + -1p * -5) = -5p + 3(1 + -1p) 2p + (-5 + 5p) = -5p + 3(1 + -1p) Reorder the terms: -5 + 2p + 5p = -5p + 3(1 + -1p) Combine like terms: 2p + 5p = 7p -5 + 7p = -5p + 3(1 + -1p) -5 + 7p = -5p + (1 * 3 + -1p * 3) -5 + 7p = -5p + (3 + -3p) Reorder the terms: -5 + 7p = 3 + -5p + -3p Combine like terms: -5p + -3p = -8p -5 + 7p = 3 + -8p Solving -5 + 7p = 3 + -8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '8p' to each side of the equation. -5 + 7p + 8p = 3 + -8p + 8p Combine like terms: 7p + 8p = 15p -5 + 15p = 3 + -8p + 8p Combine like terms: -8p + 8p = 0 -5 + 15p = 3 + 0 -5 + 15p = 3 Add '5' to each side of the equation. -5 + 5 + 15p = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 15p = 3 + 5 15p = 3 + 5 Combine like terms: 3 + 5 = 8 15p = 8 Divide each side by '15'. p = 0.5333333333 Simplifying p = 0.5333333333
| -27+4n=48 | | m/2-4=-16 | | 2y=-40 | | Ax+by=16 | | 8f=-64 | | 4y-1=6y-15 | | 3xy+18x+4y+24= | | 3x+6x-7+5-2x= | | 2p+2(1-p)=2p-2(1-p) | | 3(x-2)=9x-5 | | X+1.5y=30 | | V/18=7 | | -27+4n=36 | | d/5=-60 | | 25t=12/25 | | 24-(2c-3)=2(c+3)+c | | y+15.2=-4.5 | | 10x-4+6x=18 | | 7a+6a+7b-6b-10a= | | 3x-4.2=9.4 | | 8s-240=72 | | (6x)(3x+2)=y | | B+23m=342 | | -2p+4(1-p)=8p-2(1-p) | | 4+3a=22+a | | 4(5x+2)-8(x-6)=62 | | 2Q+D=48 | | B+10m=147 | | 7g-2h=-9 | | -2-16=3(h-2) | | 90+(5x-6)+3x=180 | | 2x+10-4x=-3 |